Biodegradable PLA composite fiber and surface modification method thereof

CN122898983APending Publication Date: 2026-10-13福建省福地新材料股份有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611392711.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

但PLA纤维存在明显技术缺陷:本征脆性大,弯折易断裂;表面能低、极性弱,与树脂基体、纺织浆料等界面结合力差;耐候性不足,紫外线下易降解老化,限制其在高端纺织与结构复合材料中的应用

Benefits of technology

本发明通过多级改性纳米二氧化硅,结合氧化镧、纳米碳酸钙、羟基磷灰石、改性综纤维素等组分协同作用,解决PLA脆性大、填料分散差问题,显著提升纤维韧性与力学强度;改性硅烷液与改进化液构建良好界面相容性,实现无机-有机相高效结合,避免功能相团聚脱落;生物质酸-金属离子协同沉积在纤维表面构建微观粗糙结构与极性涂层,降低接触角、提升界面结合力,同时增强耐候性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a biodegradable PLA composite fiber and a surface modification method thereof, and belongs to the technical field of fiber materials, and comprises the following raw materials in parts by weight: PLA chips 70-90 parts, modified nano-silicon dioxide 5-12 parts, bio-based compatilizer 3-6 parts, toughening agent 2-5 parts, antioxidant 0.3-0.8 parts, and light stabilizer 0.2-0.6 parts. The application solves the problems of large brittleness and poor filler dispersion of PLA by means of multi-stage modification of nano-silicon dioxide, combined synergistic effect of lanthanum oxide, nano-calcium carbonate, hydroxyapatite and modified cellulose, significantly improves the fiber toughness and mechanical strength, builds good interfacial compatibility between modified silane liquid and improved liquid, realizes efficient combination of inorganic-organic phases, and avoids functional phase aggregation and falling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of PLA composite fiber technology, specifically to a biodegradable PLA composite fiber and its surface modification method. Background Technology

[0002] Polylactic acid (PLA), as a typical bio-based, fully biodegradable polymer material, possesses advantages such as renewable sources, non-toxic degradation products, and moderate mechanical strength, making it promising for applications in textiles, packaging, and biomedicine. However, PLA fibers have significant technical drawbacks: high intrinsic brittleness, making them prone to breakage when bent; low surface energy and weak polarity, resulting in poor interfacial bonding with resin matrices and textile sizing agents; and insufficient weather resistance, easily degrading and aging under ultraviolet light, limiting their application in high-end textile and structural composite materials.

[0003] Current PLA modification methods mostly employ blending with single inorganic fillers or simple surface coating, which suffer from problems such as uneven filler dispersion, poor interfacial compatibility, easy detachment of functional layers, and insufficient durability of modification effects. It is difficult to simultaneously achieve toughening, interfacial reinforcement, improved weather resistance, and retention of biodegradability. Therefore, developing a PLA composite fiber that combines biodegradability, high toughness, strong interfacial bonding, and excellent weather resistance, along with its efficient surface modification method, has become a pressing technical problem to be solved in this field. Summary of the Invention

[0004] In view of the deficiencies of the prior art, the purpose of this invention is to provide a biodegradable PLA composite fiber and its surface modification method to solve the problems mentioned in the background art.

[0005] The present invention solves the technical problem by adopting the following technical solution: This invention provides a biodegradable PLA composite fiber, comprising the following raw materials by weight: 70-90 parts PLA chips, 5-12 parts modified nano silica, 3-6 parts bio-based compatibilizer, 2-5 parts toughening agent, 0.3-0.8 parts antioxidant, and 0.2-0.6 parts light stabilizer.

[0006] Preferably, the bio-based compatibilizer is maleic anhydride-grafted PLA; the toughening agent is PBAT; the antioxidant is antioxidant 1010; and the light stabilizer is UV-531.

[0007] Preferably, the modified nano-silica is prepared by: first preheating the nano-silica at 55-60℃ for 1 hour, then mixing the preheated nano-silica with the modified chemical solution at a weight ratio of 1:(5-8), then sonicating at 350-400W power for 1 hour, and finally filtering and drying to obtain the modified nano-silica.

[0008] Preferably, the improved chemical solution is prepared by adding 2-4 parts of hydroxyapatite additive to 5-8 parts of modified silane solution by weight, then adding 2-3 parts of β-cyclodextrin and 1-2 parts of 4-7% (w / w) nanocellulose aqueous solution, stirring evenly to obtain the improved chemical solution.

[0009] Preferably, the modified silane liquid is prepared by: S01: Silane coupling agent KH560, 75-85% ethanol aqueous solution, and sodium alginate powder are mixed in a weight ratio of (4-6):7:(2-3) to obtain silane body; S02: By weight, 3-5 parts of 2-5% sodium silicate solution, 1-2 parts of lanthanum oxide, and 2-3 parts of nano-calcium carbonate are mixed to obtain nano-calcium carbonate solution; the nano-calcium carbonate solution and silane are stirred and mixed at a weight ratio of 3:(5-7) to obtain modified silane solution.

[0010] Preferably, the preparation method of the hydroxyapatite additive is as follows: S11: Preheat hydroxyapatite powder at 55-60℃ for 1 hour, then mix the preheated hydroxyapatite powder with sodium citrate solution of 8-12% by mass at a weight ratio of 3:(5-7) to obtain hydroxyapatite liquid. S12: By weight, adjust the pH of 100-150 parts of 10-12% methacryloyloxypropyltrimethoxysilane ethanol solution to 3, hydrolyze for 2 hours, then add 10-15 parts of holocellulose and react at 60℃ for 3-5 hours to obtain modified holocellulose; stir the modified holocellulose and hydroxyapatite solution at a weight ratio of 3:(5-7), then filter and dry to obtain hydroxyapatite additive.

[0011] In the modified silane solution, KH560, lanthanum oxide, and nano-calcium carbonate form a uniform coating layer. β-cyclodextrin and nano-cellulose provide steric hindrance, ensuring uniform dispersion of nano-silica in the PLA matrix without significant agglomeration, thus greatly improving interfacial compatibility. Hydroxyapatite, modified holocellulose, and PLA molecular chains form strong hydrogen bonds and coordination bonds, resulting in a tight inorganic-organic interface. Under comprehensive parameter control, the PLA composite fiber exhibits a breaking strength ≥3.65 cN / dtex and a breaking elongation ≥40%, significantly improving brittleness and greatly enhancing spinnability and durability. Furthermore, the introduction of numerous polar groups such as hydroxyl, carboxyl, and siloxane bonds onto the surface of the nano-silica further enhances its effectiveness. The surface contact angle of PLA fibers was reduced to about 60 degrees, significantly increasing surface energy and greatly enhancing interfacial bonding with coatings, resins, and textile sizing agents. Lanthanum oxide, nano-calcium carbonate, hydroxyapatite, and silane coatings form a physical barrier and photostable system, effectively inhibiting the photo-oxidative degradation of PLA. After 100 hours of UV aging, the fiber strength retention rate was ≥87%, and the weather resistance was far superior to that of unmodified PLA fibers. The alkane system, hydroxyapatite, β-cyclodextrin, nanocellulose, and holocellulose used are all bio-based or components that can withstand degradation environments, and do not affect the degradation performance of PLA itself. The resulting fibers had a degradation rate of ≥89% after 90 days of soil burial, meeting the requirements for biodegradability.

[0012] Preferably, the stirring speed of the stirring process is 450-500 r / min, and the stirring time is 2 h.

[0013] This invention also provides a method for surface modification of biodegradable PLA composite fibers, comprising the following steps: S100: Blending and granulation: PLA chips, modified nano-silica, bio-based compatibilizer, toughening agent, antioxidant, and light stabilizer are mixed and melt-extruded and granulated at 170-190℃ using a twin-screw extruder to obtain modified PLA granules; S200: Melt spinning: Modified PLA granules are melt spun at 180-200℃ with a spinning speed of 800-1200m / min and a draw ratio of 3.0-4.5 to obtain biodegradable PLA composite fibers; S300: Surface modification: Biodegradable PLA composite fibers are surface modified using a biomass acid-metal ion synergistic deposition method to obtain surface-modified PLA composite fibers.

[0014] Preferably, the specific method for surface modification of S300 is as follows: S310. Immerse the fiber in a 3-5% (w / w) tannic acid aqueous solution at room temperature for 5-10 minutes, then rinse with deionized water 1-2 times. S320. Immerse the rinsed fibers in a 2-4% zinc chloride aqueous solution at room temperature for 3-5 minutes, then rinse with deionized water 1-2 times. S330. Using the above-mentioned tannic acid impregnation-rinsing-zinc chloride impregnation-rinsing as a complete deposition cycle, repeat the cycle 2-3 times, and finally dry at 60-70℃ for 1-2 hours to obtain surface-modified PLA composite fibers.

[0015] Compared with the prior art, the present invention has the following beneficial effects: This invention addresses the issues of high brittleness and poor filler dispersion in PLA by using multi-stage modified nano-silica, combined with the synergistic effects of lanthanum oxide, nano-calcium carbonate, hydroxyapatite, and modified holocellulose, significantly improving fiber toughness and mechanical strength. The modified silane liquid and improved chemical liquid create good interfacial compatibility, achieving efficient bonding between inorganic and organic phases and preventing functional phase aggregation and detachment. Biomass acid and metal ions are synergistically deposited on the fiber surface to construct a micro-rough structure and polar coating, reducing contact angle, improving interfacial adhesion, and enhancing weather resistance. Detailed Implementation

[0016] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0017] This embodiment of a biodegradable PLA composite fiber comprises the following raw materials by weight: 70-90 parts PLA chips, 5-12 parts modified nano silica, 3-6 parts bio-based compatibilizer, 2-5 parts toughening agent, 0.3-0.8 parts antioxidant, and 0.2-0.6 parts light stabilizer.

[0018] In this embodiment, the bio-based compatibilizer is maleic anhydride-grafted PLA; the toughening agent is PBAT; the antioxidant is antioxidant 1010; and the light stabilizer is UV-531.

[0019] The preparation method of modified nano-silica in this embodiment is as follows: First, the nano-silica is preheated at 55-60℃ for 1 hour. Then, the preheated nano-silica is stirred and mixed with the modified chemical liquid at a weight ratio of 1:(5-8). Then, it is ultrasonicated at 350-400W power for 1 hour. Finally, it is filtered and dried to obtain modified nano-silica.

[0020] The improved liquid preparation method of this embodiment is as follows: by weight, 2-4 parts of hydroxyapatite additive are added to 5-8 parts of modified silane liquid, followed by 2-3 parts of β-cyclodextrin and 1-2 parts of 4-7% (w / w) nanocellulose aqueous solution, and stirred evenly to obtain the improved liquid.

[0021] The preparation method of the modified silane liquid in this embodiment is as follows: S01: Silane coupling agent KH560, 75-85% ethanol aqueous solution, and sodium alginate powder are mixed in a weight ratio of (4-6):7:(2-3) to obtain silane body; S02: By weight, 3-5 parts of 2-5% sodium silicate solution, 1-2 parts of lanthanum oxide, and 2-3 parts of nano-calcium carbonate are mixed to obtain nano-calcium carbonate solution; the nano-calcium carbonate solution and silane are stirred and mixed at a weight ratio of 3:(5-7) to obtain modified silane solution.

[0022] The preparation method of the hydroxyapatite additive in this embodiment is as follows: S11: Preheat hydroxyapatite powder at 55-60℃ for 1 hour, then mix the preheated hydroxyapatite powder with sodium citrate solution of 8-12% by mass at a weight ratio of 3:(5-7) to obtain hydroxyapatite liquid. S12: By weight, adjust the pH of 100-150 parts of a 10-12% (w / w) methacryloyloxypropyltrimethoxysilane ethanol solution to 3, hydrolyze for 2 hours, then add 10-15 parts of holocellulose and react at 60℃ for 3-5 hours to obtain modified holocellulose; stir the modified holocellulose and hydroxyapatite solution at a weight ratio of 3:(5-7), then filter and dry to obtain hydroxyapatite additive. The stirring speed during the stirring process is 450-500 r / min, and the stirring time is 2 hours.

[0023] This embodiment of a surface modification method for biodegradable PLA composite fibers includes the following steps: S100: Blending and granulation: PLA chips, modified nano-silica, bio-based compatibilizer, toughening agent, antioxidant, and light stabilizer are mixed and melt-extruded and granulated at 170-190℃ using a twin-screw extruder to obtain modified PLA granules; S200: Melt spinning: Modified PLA granules are melt spun at 180-200℃ with a spinning speed of 800-1200m / min and a draw ratio of 3.0-4.5 to obtain biodegradable PLA composite fibers; S300: Surface modification: Biodegradable PLA composite fibers are surface modified using a biomass acid-metal ion synergistic deposition method to obtain surface-modified PLA composite fibers.

[0024] The specific method for surface modification of S300 in this embodiment is as follows: S310. Immerse the fiber in a 3-5% (w / w) tannic acid aqueous solution at room temperature for 5-10 minutes, then rinse with deionized water 1-2 times. S320. Immerse the rinsed fibers in a 2-4% zinc chloride aqueous solution at room temperature for 3-5 minutes, then rinse with deionized water 1-2 times. S330. Using the above-mentioned tannic acid impregnation-rinsing-zinc chloride impregnation-rinsing as a complete deposition cycle, repeat the cycle 2-3 times, and finally dry at 60-70℃ for 1-2 hours to obtain surface-modified PLA composite fibers.

[0025] Example 1: A biodegradable PLA composite fiber, comprising the following raw materials by weight: 80 parts PLA chips, 7 parts modified nano silica, 4.5 parts bio-based compatibilizer, 3.5 parts toughening agent, 0.5 parts antioxidant, and 0.4 parts light stabilizer.

[0026] In this embodiment, the bio-based compatibilizer is maleic anhydride-grafted PLA; the toughening agent is PBAT; the antioxidant is antioxidant 1010; and the light stabilizer is UV-531.

[0027] The modified nano-silica preparation method of this embodiment is as follows: first, the nano-silica is preheated at 58°C for 1 hour, then the preheated nano-silica is stirred and mixed with the modified chemical liquid at a weight ratio of 1:6.5, then ultrasonicated at 375W power for 1 hour, and finally filtered and dried to obtain modified nano-silica.

[0028] The improved liquid preparation method of this embodiment is as follows: by weight, 3 parts of hydroxyapatite additive are added to 6.5 parts of modified silane liquid, followed by 2.5 parts of β-cyclodextrin and 1.5 parts of 5.5% nanocellulose aqueous solution, and stirred evenly to obtain the improved liquid.

[0029] The preparation method of the modified silane liquid in this embodiment is as follows: S01: Silane coupling agent KH560, 80% ethanol aqueous solution, and sodium alginate powder are mixed in a weight ratio of 5:7:2.5 to obtain silane. S02: By weight, 4 parts of 3.5% sodium silicate solution, 1.5 parts of lanthanum oxide and 2.5 parts of nano calcium carbonate are mixed to obtain nano calcium carbonate solution; the nano calcium carbonate solution and silane are stirred and mixed at a weight ratio of 3:6 to obtain modified silane solution.

[0030] The preparation method of the hydroxyapatite additive in this embodiment is as follows: S11: Preheat hydroxyapatite powder at 58°C for 1 hour, then mix the preheated hydroxyapatite powder with a 10% sodium citrate solution at a weight ratio of 3:6 to obtain hydroxyapatite liquid. S12: By weight, 125 parts of an 11% (w / w) methacryloyloxypropyltrimethoxysilane ethanol solution were adjusted to pH 3 and hydrolyzed for 2 hours. Then, 12.5 parts of holocellulose were added, and the mixture was reacted at 60°C for 4 hours to obtain modified holocellulose. The modified holocellulose was then stirred with hydroxyapatite solution at a weight ratio of 3:6, followed by filtration and drying to obtain the hydroxyapatite additive. The stirring speed during the stirring process was 475 r / min, and the stirring time was 2 hours.

[0031] This embodiment of a surface modification method for biodegradable PLA composite fibers includes the following steps: S100: Blending and granulation: PLA chips, modified nano-silica, bio-based compatibilizer, toughening agent, antioxidant, and light stabilizer are mixed and melt-extruded and granulated at 180°C using a twin-screw extruder to obtain modified PLA granules; S200: Melt spinning: Modified PLA granules are melt spun at 190℃ with a spinning speed of 1000m / min and a draw ratio of 4.0 to obtain biodegradable PLA composite fibers; S300: Surface modification: Biodegradable PLA composite fibers are surface modified using a biomass acid-metal ion synergistic deposition method to obtain surface-modified PLA composite fibers.

[0032] The specific surface modification method in this embodiment is as follows: S310. Immerse the fiber in a 4% (w / w) tannic acid aqueous solution at room temperature for 7.5 minutes, then rinse once with deionized water. S320. Immerse the rinsed fibers in a 3% zinc chloride aqueous solution at room temperature for 4 minutes, then rinse once with deionized water. S330. Using the above-mentioned tannic acid impregnation-rinsing-zinc chloride impregnation-rinsing as a complete deposition cycle, repeat the cycle twice, and finally dry at 65°C for 1.5 h to obtain surface-modified PLA composite fibers.

[0033] Example 2: A biodegradable PLA composite fiber, comprising the following raw materials by weight: 70 parts PLA chips, 5 parts modified nano silica, 3 parts bio-based compatibilizer, 2 parts toughening agent, 0.3 parts antioxidant, and 0.2 parts light stabilizer.

[0034] In this embodiment, the bio-based compatibilizer is maleic anhydride-grafted PLA; the toughening agent is PBAT; the antioxidant is antioxidant 1010; and the light stabilizer is UV-531.

[0035] The modified nano-silica preparation method of this embodiment is as follows: First, the nano-silica is preheated at 55°C for 1 hour. Then, the preheated nano-silica is stirred and mixed with the modified chemical liquid at a weight ratio of 1:5. Then, it is ultrasonicated at 350W power for 1 hour. Finally, it is filtered and dried to obtain the modified nano-silica.

[0036] The improved liquid preparation method of this embodiment is as follows: by weight, 2 parts of hydroxyapatite additive are added to 5 parts of modified silane liquid, followed by 2 parts of β-cyclodextrin and 1 part of 4% (w / w) nanocellulose aqueous solution, and stirred evenly to obtain the improved liquid.

[0037] The preparation method of the modified silane liquid in this embodiment is as follows: S01: Silane coupling agent KH560, 75% ethanol aqueous solution, and sodium alginate powder are mixed in a weight ratio of 4:7:2 to obtain silane. S02: By weight, 3 parts of 2% sodium silicate solution, 1 part of lanthanum oxide and 2 parts of nano calcium carbonate are mixed to obtain nano calcium carbonate solution; the nano calcium carbonate solution and silane are stirred and mixed at a weight ratio of 3:5 to obtain modified silane solution.

[0038] The preparation method of the hydroxyapatite additive in this embodiment is as follows: S11: Preheat hydroxyapatite powder at 55°C for 1 hour, then mix the preheated hydroxyapatite powder with 8% sodium citrate solution at a weight ratio of 3:5 to obtain hydroxyapatite liquid. S12: By weight, 100 parts of a 10% (w / w) methacryloyloxypropyltrimethoxysilane ethanol solution were adjusted to pH=3 and hydrolyzed for 2 hours. Then, 10 parts of holocellulose were added, and the mixture was reacted at 60℃ for 3 hours to obtain modified holocellulose. The modified holocellulose was then stirred with hydroxyapatite solution at a weight ratio of 3:5, followed by filtration and drying to obtain hydroxyapatite additive. The stirring speed during the stirring process was 450 r / min, and the stirring time was 2 hours.

[0039] This embodiment of a surface modification method for biodegradable PLA composite fibers includes the following steps: S100: Blending and granulation: PLA chips, modified nano-silica, bio-based compatibilizer, toughening agent, antioxidant, and light stabilizer are mixed and melt-extruded and granulated at 170°C using a twin-screw extruder to obtain modified PLA granules; S200: Melt spinning: Modified PLA granules are melt spun at 180℃ with a spinning speed of 800m / min and a draw ratio of 3.0 to obtain biodegradable PLA composite fibers; S300: Surface modification: Biodegradable PLA composite fibers are surface modified using a biomass acid-metal ion synergistic deposition method to obtain surface-modified PLA composite fibers.

[0040] The specific surface modification method in this embodiment is as follows: S310. Immerse the fiber in a 3% (w / w) tannic acid aqueous solution at room temperature for 5 minutes, then rinse it once with deionized water. S320. Immerse the rinsed fibers in a 2% zinc chloride aqueous solution at room temperature for 3 minutes, then rinse once with deionized water. S330. Using the above-mentioned tannic acid impregnation-rinsing-zinc chloride impregnation-rinsing as a complete deposition cycle, repeat the cycle twice, and finally dry at 60°C for 1 hour to obtain surface-modified PLA composite fibers.

[0041] Example 3: A biodegradable PLA composite fiber, comprising the following raw materials by weight: 90 parts PLA chips, 12 parts modified nano silica, 6 parts bio-based compatibilizer, 5 parts toughening agent, 0.8 parts antioxidant, and 0.6 parts light stabilizer.

[0042] In this embodiment, the bio-based compatibilizer is maleic anhydride-grafted PLA; the toughening agent is PBAT; the antioxidant is antioxidant 1010; and the light stabilizer is UV-531.

[0043] The modified nano-silica preparation method of this embodiment is as follows: First, the nano-silica is preheated at 60°C for 1 hour. Then, the preheated nano-silica is stirred and mixed with the modified chemical liquid at a weight ratio of 1:8. Then, it is ultrasonicated at 400W power for 1 hour. Finally, it is filtered and dried to obtain the modified nano-silica.

[0044] The improved liquid preparation method of this embodiment is as follows: by weight, 4 parts of hydroxyapatite additive are added to 8 parts of modified silane liquid, followed by 3 parts of β-cyclodextrin and 2 parts of 7% (w / w) nanocellulose aqueous solution, and stirred evenly to obtain the improved liquid.

[0045] The preparation method of the modified silane liquid in this embodiment is as follows: S01: Silane coupling agent KH560, 85% ethanol aqueous solution, and sodium alginate powder are mixed in a weight ratio of 6:7:3 to obtain silane. S02: By weight, 5 parts of 5% sodium silicate solution, 2 parts of lanthanum oxide and 3 parts of nano calcium carbonate are mixed to obtain nano calcium carbonate solution; the nano calcium carbonate solution and silane are stirred and mixed at a weight ratio of 3:7 to obtain modified silane solution.

[0046] The preparation method of the hydroxyapatite additive in this embodiment is as follows: S11: Preheat hydroxyapatite powder at 60°C for 1 hour, then mix the preheated hydroxyapatite powder with a 12% sodium citrate solution at a weight ratio of 3:7 to obtain hydroxyapatite liquid. S12: By weight, 150 parts of a 12% (w / w) methacryloyloxypropyltrimethoxysilane ethanol solution were adjusted to pH 3 and hydrolyzed for 2 hours. Then, 15 parts of holocellulose were added, and the mixture was reacted at 60°C for 5 hours to obtain modified holocellulose. The modified holocellulose was then stirred with hydroxyapatite solution at a weight ratio of 3:5, followed by filtration and drying to obtain the hydroxyapatite additive. The stirring speed during the stirring process was 500 r / min, and the stirring time was 2 hours.

[0047] This embodiment of a surface modification method for biodegradable PLA composite fibers includes the following steps: S100: Blending and granulation: PLA chips, modified nano-silica, bio-based compatibilizer, toughening agent, antioxidant, and light stabilizer are mixed and melt-extruded and granulated at 190°C using a twin-screw extruder to obtain modified PLA granules; S200: Melt spinning: Modified PLA granules are melt spun at 200℃ with a spinning speed of 1200m / min and a draw ratio of 4.5 to obtain biodegradable PLA composite fibers; S300: Surface modification: Biodegradable PLA composite fibers are surface modified using a biomass acid-metal ion synergistic deposition method to obtain surface-modified PLA composite fibers.

[0048] The specific method for surface modification of S300 in this embodiment is as follows: S310. Immerse the fiber in a 5% (w / w) tannic acid aqueous solution at room temperature for 10 minutes, then rinse twice with deionized water. S320. Immerse the rinsed fibers in a 4% zinc chloride aqueous solution at room temperature for 5 minutes, then rinse twice with deionized water. S330. Using the above-mentioned tannic acid impregnation-rinsing-zinc chloride impregnation-rinsing as a complete deposition cycle, repeat the cycle 3 times, and finally dry at 70℃ for 2 hours to obtain surface-modified PLA composite fibers.

[0049] Comparative Example 1: Unlike Example 1, no β-cyclodextrin and nanocellulose aqueous solution were added.

[0050] Comparative Example 2: Unlike Example 1, no nano-calcium carbonate solution was added during the preparation of the modified silane solution.

[0051] Comparative Example 3: Unlike Example 1, hydroxyapatite additive was not added in the preparation of the improved solution.

[0052] Comparative Example 4: Unlike Example 1, no modified holocellulose was added in the preparation of the hydroxyapatite additive.

[0053] Comparative Example 5: Unlike Example 1, the PLA composite fibers did not undergo surface modification treatment.

[0054] The surface-modified PLA composite fiber products of Examples 1-3 and Comparative Examples 1-5 were subjected to performance tests, and the performance test results are shown in Table 1.

[0055] The testing standards are as follows: The breaking strength and elongation at break were tested according to GB / T14337-2008. The specimen length was 20 mm, the tensile speed was 20 mm / min, the pre-tension was 0.05 cN / dtex, and 20 tests were performed in each group to take the average value. The surface contact angle was measured using an optical contact angle meter according to GB / T30693-2014. The volume of the deionized water droplet was 5 μL, and the reading was taken after standing at room temperature for 5 seconds. Five points were measured in each group and the average value was taken. Weather resistance was tested according to GB / T16422.3-2014 using fluorescent ultraviolet aging, with UVA at 340nm and an irradiation intensity of 0.89W / (m²). 2 •nm), strength retention rate was tested after aging for 100 hours; The biodegradation rate was determined by soil burial degradation test according to GB / T20197-2017, with a temperature of 25±2℃ and a humidity of 60±5%. The mass loss degradation rate was calculated after 90 days of degradation.

[0056] Table 1 Performance Test Results:

[0057] As can be seen from Comparative Examples 1-5 and Examples 1-3, the surface-modified PLA composite fiber products of Examples 1-3 have excellent breaking strength and breaking elongation, while the contact angle, UV resistance and degradation can be improved in a coordinated manner. This invention does not add β-cyclodextrin and nano-cellulose aqueous solution, does not add nano-calcium carbonate solution in the preparation of modified silane solution, does not add hydroxyapatite additive in the preparation of improved chemical solution, does not add modified holocellulose in the preparation of hydroxyapatite additive, and the PLA composite fiber does not undergo surface modification treatment. The performance of the products all tend to deteriorate to varying degrees. The product raw materials obtained by the specific method of this invention have the most significant performance effect. The effect of other methods is not as significant as that of this invention. At the same time, the surface modification treatment of PLA composite fiber also has an improving effect on the performance of the product.

[0058] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0059] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A biodegradable PLA composite fiber, characterized in that, The raw materials include the following by weight: 70-90 parts PLA chips, 5-12 parts modified nano silica, 3-6 parts bio-based compatibilizer, 2-5 parts toughening agent, 0.3-0.8 parts antioxidant, and 0.2-0.6 parts light stabilizer; The modified nano silica is prepared by: first preheating the nano silica at 55-60℃ for 1 hour, then mixing the preheated nano silica with the modified chemical liquid at a weight ratio of 1:(5-8), then sonicating at 350-400W power for 1 hour, and finally filtering and drying to obtain the modified nano silica. The improved chemical solution is prepared by adding 2-4 parts of hydroxyapatite additive to 5-8 parts of modified silane solution by weight, then adding 2-3 parts of β-cyclodextrin and 1-2 parts of 4-7% (w / w) nanocellulose aqueous solution, stirring evenly to obtain the improved chemical solution.

2. The biodegradable PLA composite fiber according to claim 1, characterized in that, The bio-based compatibilizer is maleic anhydride-grafted PLA; the toughening agent is PBAT; the antioxidant is antioxidant 1010; and the light stabilizer is UV-531.

3. The biodegradable PLA composite fiber according to claim 1, characterized in that, The method for preparing the modified silane liquid is as follows: S01: Silane coupling agent KH560, 75-85% ethanol aqueous solution, and sodium alginate powder are mixed in a weight ratio of (4-6):7:(2-3) to obtain silane body; S02: By weight, 3-5 parts of 2-5% sodium silicate solution, 1-2 parts of lanthanum oxide, and 2-3 parts of nano-calcium carbonate are mixed to obtain nano-calcium carbonate solution; the nano-calcium carbonate solution and silane are stirred and mixed at a weight ratio of 3:(5-7) to obtain modified silane solution.

4. The biodegradable PLA composite fiber according to claim 1, characterized in that, The preparation method of the hydroxyapatite additive is as follows: S11: Preheat hydroxyapatite powder at 55-60℃ for 1 hour, then mix the preheated hydroxyapatite powder with sodium citrate solution of 8-12% by mass at a weight ratio of 3:(5-7) to obtain hydroxyapatite liquid. S12: By weight, adjust the pH of 100-150 parts of 10-12% methacryloyloxypropyltrimethoxysilane ethanol solution to 3, hydrolyze for 2 hours, then add 10-15 parts of holocellulose and react at 60℃ for 3-5 hours to obtain modified holocellulose. Modified holocellulose and hydroxyapatite liquid were stirred at a weight ratio of 3:(5-7), then filtered and dried to obtain hydroxyapatite additive.

5. The biodegradable PLA composite fiber according to claim 4, characterized in that, The stirring speed for the stirring process is 450-500 r / min, and the stirring time is 2 h.

6. A method for surface modification of biodegradable PLA composite fibers, used to modify the surface of a biodegradable PLA composite fiber as described in any one of claims 1-5, characterized in that, Includes the following steps: S100: Blending and granulation: PLA chips, modified nano-silica, bio-based compatibilizer, toughening agent, antioxidant, and light stabilizer are mixed and melt-extruded and granulated at 170-190℃ using a twin-screw extruder to obtain modified PLA granules; S200: Melt spinning: Modified PLA granules are melt spun at 180-200℃ with a spinning speed of 800-1200m / min and a draw ratio of 3.0-4.5 to obtain biodegradable PLA composite fibers; S300: Surface modification: Biodegradable PLA composite fibers are surface modified using a biomass acid-metal ion synergistic deposition method to obtain surface-modified PLA composite fibers.

7. The surface modification method for biodegradable PLA composite fibers according to claim 6, characterized in that, The specific methods for surface modification of S300 are as follows: S310. Immerse the fiber in a 3-5% (w / w) tannic acid aqueous solution at room temperature for 5-10 minutes, then rinse with deionized water 1-2 times. S320. Immerse the rinsed fibers in a 2-4% zinc chloride aqueous solution at room temperature for 3-5 minutes, then rinse with deionized water 1-2 times. S330. Using the above-mentioned tannic acid impregnation-rinsing-zinc chloride impregnation-rinsing as a complete deposition cycle, repeat the cycle 2-3 times, and finally dry at 60-70℃ for 1-2 hours to obtain surface-modified PLA composite fibers.